A Selective β−Catenin‐Metadherin/CEACAM1‐CCL3 Axis Mediates Metastatic Heterogeneity upon Tumor–Macrophage Interaction. Issue 16 (11th April 2022) - To, Sally K. Y.; Tang, Maggie K. S.; Tong, Yin; Zhang, Jiangwen; Chan, Karen K. L.; Ip, Philip P. C.; Shi, Jue; Wong, Alice S. T.
Abstract: Tumor heterogeneity plays a key role in cancer relapse and metastasis, however, the distinct cellular behaviors and kinetics of interactions among different cancer cell subclones and the tumor microenvironment are poorly understood. By profiling an isogenic model that resembles spontaneous human ovarian cancer metastasis with an highly metastatic (HM) and non‐metastatic (NM) tumor cell pair, one finds an upregulation of Wnt/ β ‐catenin signaling uniquely in HM. Using humanized immunocompetent mice, one shows for the first time that activated β ‐catenin acts nonautonomously to modulate the immune microenvironment by enhancing infiltrating tumor‐associated macrophages (TAM) at the metastatic site. Single‐cell time‐lapse microscopy further reveals that upon contact with macrophages, a significant subset of HM, but not NM, becomes polyploid, a phenotype pivotal for tumor aggressiveness and therapy resistance. Moreover, HM, but not NM, polarizes macrophages to a TAM phenotype. Mechanistically, β ‐catenin upregulates cancer cell surface metadherin, which communicates through CEACAM1 expressed on macrophages to produce CCL3. Tumor xenografts in humanized mice and clinical patient samples both corroborate the relevance of enhanced metastasis, TAM activation, and polyploidy in vivo. The results thus suggest that targeting the β ‐catenin‐metadherin/CEACAM1‐CCL3 positive feedback cascade holds great therapeutic potential to disrupt polyploidization of the cancer subclones that drive metastasis. Abstract : Macrophages are closely associated with cancer metastasis. Using an isogenic humanized mouse model, this study demonstrates that metastatic ovarian cancer cells can enhance the tumor‐promoting phenotypes of macrophages in contact. It further reports a novel phenomenon that these macrophages could reciprocally induce polyploidy in a subset of the metastatic cancer cells to promote tumor aggressiveness.